(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Craving is a persistent factor in addictive behaviors. The aim of study was to investigate the effectiveness of matrix interventions in reducing the difficulty in cognitive emotion regulation and craving in methamphetamine-dependent patients.Methods: The research method was experimental and the research design was pre and posttest with the control group. The statistical population of the study consisted of all methamphetamine-dependent patients who visited the Golestan hospital of Ahvaz in 2019. Among them, 40 ones were selected by a purposive sampling method and were randomly classified into experimental and control groups (n = 20 per group). The Cognitive Emotion Regulation and Craving Questionnaires were used for data collection. The experimental group received the matrix program (24 fifty-minute sessions), but the control group did not receive any intervention. Data were analyzed by the analysis of covariance (ANCOVA). Significant level was set at 0.05.Results: The results indicated that the matrix program was effective in reducing the difficulty in cognitive emotion regulation (F = 13.483, Pvalue < 0.001). The research results also indicated that the matrix program was effective in reducing craving in methamphetaminedependent patients (F = 60.716, Pvalue < 0.001).Conclusions: According to results, the therapy could be used to reduce the difficulty in cognitive emotion regulation and craving in methamphetamine-dependent patients. Keywords: Matrix model, Cognitive emotion regulation, Craving, Methamphetamine.